A randomized study of hexaminolevulinate photodynamic therapy in patients with cervical intraepithelial neoplasia 1/2 - Hillemanns, Peter; Garcia, Francisco; Petry, Karl Ulrich; Dvorak, Vladimír; Sadovsky, Oliver; Iversen, Ole-Erik; Einstein, Mark H (American journal of obstetrics and gynecology, 2015)
OBJECTIVE: The objective of the study was to investigate the efficacy and safety of hexaminolevulinate (HAL) photodynamic therapy (PDT), a novel therapy for women with cervical intraepithelial neoplasia (CIN)1/2, to define the appropriate population and endpoints for a phase 3 program. STUDY DESIGN: This was a double-blind, randomized, placebo-controlled, dose-finding study that included a total of 262 women with biopsy-confirmed CIN 1/2 based on local pathology. Patients received 1 or 2 topical treatments of HAL hydrochloride 0.2%, 1%, 5%, and placebo ointment and were evaluated for response after 3-6 months based on biopsy, Papanicolaou test, and oncogenic human papillomavirus (HPV) test. All efficacy analyses were performed on blinded central histology review to avoid interreader variability. Adverse events, blood biochemistry, and vital signs were assessed after 3 months. RESULTS: There were no statistically significant differences between placebo and either the CIN 1 or combined CIN 1/2 populations. A clear dose effect with a statistically significant response in the HAL 5% group of 95% (18/19 patients) compared to 57% (12/21 patients) in the placebo group (P < .001) was observed at 3 months in women with CIN 2, including an encouraging 83% (5/6 patients) clearance of HPV 16/18 compared to 33% (2/6 patients) in the placebo group at 6 months. The treatment was easy to use and well accepted by patients and gynecologists. Only local self-limiting adverse reactions including discharge, discomfort, and spotting were reported. CONCLUSION: HAL PDT is a novel therapy that shows promise in the treatment of CIN 2 including clearance of oncogenic HPV, but not of CIN 1. The positive risk/benefit balance makes HAL PDT a tissue-preserving alternative in women of childbearing age who wish to preserve the cervix. Confirmatory studies are planned.
Keywords: Aminolevulinic Acid; fotosenzibilizující látky; Humans; kyselina aminolevulová; lidé středního věku; analýza podle původního léčebného záměru; Double-Blind Method; Photosensitizing Agents; Administration, Topical; Drug Administration Schedule; Dose-Response Relationship, Drug; Female; mladý dospělý; dospělí; nádory děložního čípku; výsledek terapie; dvojitá slepá metoda; lidé; fotochemoterapie; Adult; ženské pohlaví; Middle Aged; dysplazie děložního hrdla; Adolescent; Treatment Outcome; Intention to Treat Analysis; Photochemotherapy; Uterine Cervical Neoplasms; Young Adult; Uterine Cervical Dysplasia; vztah mezi dávkou a účinkem léčiva; aplikace lokální; rozvrh dávkování léků; mladiství